Managerial Leadership: An Islamic Perspective (IIUC Studies, 2009)
Islam is the guide to eradicate all problems in our social life. Allah (Swt) has addressed the believers as Ummah, which implies the necessity of leadership in Islam. Allah says to his Prophet Mohammad (Sm) "...I have perfected your religion for you, completed My favor upon you, and have chosen for you Islam as your religion" (Surah Al-Maidah). Mohammad (Sm) says "Every one of you is a shepherd and every one of you is responsible for what he is shepherd of" (Sahih Al Bukhari). Islam as a complete code of life has a set of principles, guidelines for managers to lead the human resources in an organization. This study is an attempt to find out the basic guidelines laid down in Islam for managerial leadership. It has pointed out the operational principles of managerial leadership, managerial grid theory, leadership continuum, team building- team spirit and qualities of a managerial leader from the Islam perspective.   doi: 10.3329/iiucs.v4i0.2688     IIUC STUDIES Vol. - 4, December 2007 (p 7-24)